Managing your own learning - Davis, James R. 1936- (Berrett-Koehler Publishers, 2000)
In today's knowledge-based society, where intellectual capital is an organization's most competitive asset, learning is serious business. Effective Training Strategies offers a comprehensive approach to creating a focused philosophy of learning, choosing the best approach to planning programs and activities, and developing appropriate systems for assessing results. Davis and Davis describe seven powerful training strategies.
Includes bibliographical references (pages 201-211) and index. - Print version record
Keywords: Adult learning; Self-culture; Apprentissage adulte; Autodidaxie; EDUCATION; Adult & Continuing Education; EDUCATION; Non-Formal Education; Learning; Success in business